Directional passive ambient air monitoring of ammonia for fugitive source attribution; a field trial with wind tunnel characteristics. (October 2017) - Solera García, M.A.; Timmis, R.J.; Van Dijk, N.; Whyatt, J.D.; Leith, I.D.; Leeson, S.R.; Braban, C.F.; Sheppard, L.J.; Sutton, M.A.; Tang, Y.S.
Abstract: Atmospheric ammonia is a precursor for secondary particulate matter formation, which harms human health and contributes to acidification and eutrophication. Under the 2012 Gothenburg Protocol, 2005 emissions must be cut by 6% by 2020. In the UK, 83% of total emissions originate from agricultural practices such as fertilizer use and rearing of livestock, with emissions that are spatially extensive and variable in nature. Such fugitive emissions make resolving and tracking of individual site performance challenging. The Directional Passive Air quality Sampler (DPAS) was trialled at Whim Bog, an experimental site with a wind-controlled artificial release of ammonia, in combination with CEH-developed ammonia samplers. Whilst saturation issues were identified, two DPAS-MANDE (Mini Annular Denuder) systems, when deployed in parallel, displayed an average relative deviation of 15% (2–54%) across all 12 directions, with the directions exposed to the ammonia source showing ∼5% difference. The DPAS-MANDE has shown great potential for directional discrimination and can contribute to the understanding and management of fugitive ammonia sources from intensive agriculture sites. Highlights: A Directional Passive Air Sampler (DPAS) is proposed for ambient ammonia monitoring. The DPAS was tested in the field with a wind-dependent artificial release of ammonia. The sampling of the DPAS-MANDE system showed distinct directional discrimination. The MANDEs within the DPAS are subject to diffusional interference and can saturate. The DPAS-MANDE system may be used to identify and target fugitive sources of ammonia.